Papillary Thyroid Carcinoma Landscape and Its Immunological Link With Hashimoto Thyroiditis at Single-Cell Resolution - Pan, Jun; Ye, Fang; Yu, Chengxuan; Zhu, Qinsheng; Li, Jiaqi; Zhang, Yaohui; Tian, Hedi; Yao, Yunjin; Zhu, Minjie; Shen, Yibin; Zhu, Feng; Wang, Yingying; et al. (Frontiers in Cell and Developmental Biology, 2021)
The tumor microenvironment (TME) heterogeneity of papillary thyroid cancer (PTC) is poorly characterized. The relationship between PTC and Hashimoto’s thyroiditis (HT) is also in doubt. Here, we employed single-cell RNA sequencing to map the transcriptome landscape of PTC from 8 PTC patients, of which 3 were concurrent with HT. Predicted copy number variation in epithelial cells and mesenchymal cells revealed the distinct molecular signatures of carcinoma cells. Carcinoma cells demonstrated intertumoral heterogeneity based on BRAF V600E mutation or lymph node metastasis, and some altered genes were identified to be correlated with disease-free survival (DFS) in The Cancer Genome Atlas (TCGA) datasets. Additionally, transcription factors regulons of follicular epithelial cells unveil the different transcription activation state in PTC patients with or without concurrent HT. The immune cells in tumors exhibited distinct transcriptional states and the presence of tumor-infiltrating B lymphocytes was predominantly linked to concurrent HT origin. Trajectory analysis of B cells and plasma cells suggested their migration potential from HT adjacent tissues to tumor tissues. Furthermore, we revealed diverse ligand-receptor pairs between non-immune cells, infiltrating myeloid cells and lymphocytes. Our results provided a single cell landscape of human PTC. These data would deepen the understanding of PTC as well as the immunological link between PTC and HT.